The effect of paddle stroke variables measured by Trainesense SmartPaddle® on the velocity of the kayak - Löppönen, A.; Vänttinen, T.; Haverinen, M.; Linnamo, V. (Sensors, 2022)
Background: This study aimed to compare key variables of paddle stroke measured by a commercial Trainesense SmartPaddle® against the strain-gauge shaft and investigate how these variables are associated with the velocity of the boat among national-level canoe polo players. Methods: This study involved 14 Finnish national-level canoe polo players. The measurement protocol consisted of three different paddling velocities, which were performed in indoor swimming pools. The velocity of the boat was calculated based on the performance time measured with the laser photocell gate. Canoe polo equipment was used in the study and a SmartPaddle sensor was attached to the paddle blade. A strain-gauge paddle shaft was used as a reference method to examine the validity of SmartPaddle. Results: The stroke rate, force production time, mean and maximal force measured with the strain-gauge paddle shaft correlated strongly (r = 0.84-0.95, p < 0.01) with SmartPaddle. However, the SmartPaddle overestimated the maximum force compared to the strain-gauge shaft. Stroke rate (r = 0.86, p < 0.01), mean force (r = 0.79, p < 0.01), maximal force (r = 0.78, p < 0.01) and total absolute impulse (r = 0.70, p < 0.01) correlated positively and force production time negatively (r = -0.76, p < 0.01) with the velocity of the boat. Conclusions: We conclude that the SmartPaddle provides promising information on stroke key variables when compared to the strain-gauge paddle shaft. The SmartPaddle is a new and interesting tool for biomechanical research and daily kayaking coaching in real open water conditions. However, more research and algorithm development are needed before the SmartPaddle can be used in everyday coaching sessions in kayaking